Green Accounting Concepts and Practices Towards Measuring Environmental Sustainability and Sustainable Business Value - Herawaty Tetty Sudarminto; Puji Harto (International Journal of Science and Society, 2023)
This article discusses the concepts and practices of environmentally friendly accounting and their impact on environmental sustainability and sustainable business value. The concept of sustainability in business and environmental challenges in the Indonesian context is the main focus. Green accounting practices include reducing carbon emissions, efficient use of natural resources, and better management of industrial waste. Positive impacts include reduced carbon emissions, more efficient use of natural resources and better waste management. Companies that adopt this practice gain benefits in the form of improved reputation, operational efficiency, and competitive advantage. The article also notes that green accounting practices are not a one-size-fits-all approach to companies and must be adapted to each context. With technological developments, increasingly stringent regulations, and public awareness of environmental issues, green accounting practices will remain an integral part of sustainable business strategies in the future.